2016
DOI: 10.26877/jitek.v2i2/nov.1206
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Dan Analisis Sensorik Produk Tahu dengan Koagulan Alami

Abstract: AbstrakTahu merupakan produk olahan kedelai yang banyak dikonsumsi di Asia. Tahu diperoleh dari proses koagulasi susu kedelai menggunakan koagulan. Umumnya koagulan yang digunakan dalam proses pembuatan tahu adalah garam (CaCl 2 , CaSO 4 , MgCl 2 ) dan asam (Asam asetat, Glukano δ-lactone (GDL)). Dalam penelitian ini dilakukan pembuatan tahu menggunakan koagulan alami belimbing wuluh, jeruk nipis dan larutan chitosan. Produk tahu yang diperoleh dibandingkan dengan produk tahu dengan penggunaan koagulan komersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
5
0
3
Order By: Relevance
“…These two bacteria will produce lactic acid that will react with the protein contained in soybeans which results in the clumping of tofu. During the incubation process, the acid produced will donate H+ ions so that if it reacts then the negatively charged protein functional groups could change the environment of the solution to be neutral and cause the protein clumping, also reduce the possibility of protein to dissolve in water during the incubation process [25]. According to Poedjiadi and Supriyanti [26], protein that has been denatured and has gone through the clumping process even though it had reached the isoelectric point, it is still possible to dissolve in tofu's whey if the pH of the tofu is outside of the isoelectric point.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These two bacteria will produce lactic acid that will react with the protein contained in soybeans which results in the clumping of tofu. During the incubation process, the acid produced will donate H+ ions so that if it reacts then the negatively charged protein functional groups could change the environment of the solution to be neutral and cause the protein clumping, also reduce the possibility of protein to dissolve in water during the incubation process [25]. According to Poedjiadi and Supriyanti [26], protein that has been denatured and has gone through the clumping process even though it had reached the isoelectric point, it is still possible to dissolve in tofu's whey if the pH of the tofu is outside of the isoelectric point.…”
Section: Resultsmentioning
confidence: 99%
“…For the texture and colour analysis of tofu from Table 2, the result showed that the highest texture is obtained by control tofu and tofu with the pH of 5 with the pressure or force of 1.95 N and 1.78 N, respectively. The tofu texture depends on the network formed by soy protein so that it can supply a compact and sturdy texture [25]. According to Meyza et al [31], the water content of tofu affects the texture value produced.…”
Section: Resultsmentioning
confidence: 99%
“…. Tahu dijadikan sebagai salah satu sumber protein bagi tubuh, serta saat ini telah banyak dikonsumsi oleh masyarakat Asia, disamping memiliki harga yang ekonomis tahu juga memiliki nilai kandungan protein yang tinggi (Arianti, 2016) [3]…”
Section: Pendahuluanunclassified
“…Ada beberapa jenis koagulan untuk proses koagulasi yaitu garam (CaCL 2 , CaSO 4 , MgCl 2 ) proteinase dan asam (asam asetat, asam sitrat, glukano δ-lactone). Pada jenis koagulan yang berbahan dasar asam seperti asam laktat, asam sitrat dan asam asetat, rendemen yang dihasilkan akan rendah, dengan tekstur tahu yang rapuh (mudah hancur) dengan flavor yang agak asam (Aryanti et al, 2016). Salah satu koagulan asam yang dapat digunakan yaitu jeruk nipis.…”
Section: Pendahuluanunclassified